2021
DOI: 10.3389/fphar.2021.707859
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Changes in Glial Cells Isolated From Rats Subjected to the Valproic Acid Model of Autism Spectrum Disorder

Abstract: Synaptic alterations concomitant with neuroinflammation have been described in patients and experimental models of autism spectrum disorder (ASD). However, the role of microglia and astroglia in relation to synaptic changes is poorly understood. Male Wistar rats prenatally exposed to valproic acid (VPA, 450 mg/kg, i.p.) or saline (control) at embryonic day 10.5 were used to study synapses, microglia, and astroglia in the prefrontal cortex (PFC) at postnatal days 3 and 35 (PND3 and PND35). Primary cultures of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…No differences were observed following exposure to VPA or α-HBCDD in comparison to controls. These results are consistent with those of Traetta et al [45] and Bronzuoli et al [44], who also concluded that Iba1 was not affected at PND35 in the VPA model. Subsequently, we examined the glial fibrillary acidic protein (GFAP) and S100-β as markers of astrocytes, known to play a crucial role in brain homeostasis and neuronal and synapse function [53,54].…”
Section: Neuroglia and Synaptic Plasticity In The Cortexsupporting
confidence: 92%
See 3 more Smart Citations
“…No differences were observed following exposure to VPA or α-HBCDD in comparison to controls. These results are consistent with those of Traetta et al [45] and Bronzuoli et al [44], who also concluded that Iba1 was not affected at PND35 in the VPA model. Subsequently, we examined the glial fibrillary acidic protein (GFAP) and S100-β as markers of astrocytes, known to play a crucial role in brain homeostasis and neuronal and synapse function [53,54].…”
Section: Neuroglia and Synaptic Plasticity In The Cortexsupporting
confidence: 92%
“…This increase was greater for α-HBCDD and was 31% higher than the VPA group (p < 0.05). An increase in this pre-synaptic protein following exposure to VPA was already demonstrated at PND35 in the prefrontal cortex (PFC) of rats [43,45] and more generally in the whole cortex [46]. Here, the α-HBCDD induced increase was even greater than that of VPA, showing a higher number of synapses and/or synaptic vesicles.…”
Section: Neuroglia and Synaptic Plasticity In The Cortexmentioning
confidence: 70%
See 2 more Smart Citations
“…The focus on the immune dysregulation in ASD and the use of models such as MIA and prenatal exposure to VPA, allow us to emphasize the importance of both heritable and environmental factors during critical developmental periods. Interestingly, microglia isolated from animals that underwent the VPA model of ASD showed high reactive morphology and increased resistance to stimulation-induced phagocytosis (Traetta et al, 2021). The postnatal administration of the non-psychoactive phytocannabinoid cannabidivarin (CBDV) in rats underwent prenatal VPA exposure induced a recovery in the hippocampus of both glial fibrillary acidic protein (GFAP) and CD11b expression, as markers of astrocytes and microglia activation, respectively (Zamberletti et al, 2019).…”
Section: Endocannabinoids-microbiota Reciprocal Contamination: Asd Ne...mentioning
confidence: 99%